Fruit and berry composition in dairy products for military personnel - Simahina, Galina; Kaminska (Halapsina), Svitlana; Bashta (Sheremet), Alla; Naumenko, Nataliia (My University, 2016)
The impact of complicated conditions of environment on the organism of soldiers is not studied well by now. Practical absence of up-to-date researches of functional possibilities of a soldier’s organism in the conditions adequate to those experienced in ATO zone requires the proper attention; otherwise the bad environment may essentially worsen the soldiers’ health. The most efficient way to deal with this situation is creating foodstuffs with biocomponents supposed to be able to protect the soldier’s organism, to optimize his functional state, and to mobilize the natural powers of the organism. The specimen of such a product is the new sort of yoghurt with fruit-and-berry filling, designed by authors of the article.
Keywords: кафедра технології оздоровчих продуктів; плоди; ягоди; раціон військовослужбовців; молочні продукти; функціональні продукти; плоды; ягоды; рацион военнослужащих; молочные продукты; функциональные продукты; fruit; berries; diet for military personnel; dairy products; functional foodstuffs; кафедра іноземних мов професійного спрямування